THE UPBRINGING OF VOLITIONAL QUALITIES BY MEANS OF TENNIS AMONG THE STUDENTS OF NON-SPORTS PROFILE UNIVERSITIES - Burlaka, I. V.; Lukachyna, A. V. (Rehabilitation and Recreation, 2021)
The upbringing of volitional qualities by means of tennis among the students of non-sports profile universities. The study provides a theoretical substantiation and analysis of methods for the formation of volitional qualities among students of non-sporting profile universities, namely, the definition of pedagogical conditions, forms and methods of forming boldness, self-affirmation and independence when playing tennis. The analysis of the psychological and pedagogical literature sources on the problem of for mation of volitional qualities of student youth, who are not in studying professional sports has been carried out. Boldness, self-affirmation and independence are defined as volitional qualities that can be used by students to mobilize their knowledge, skills and strength to overcome difficulties and obstacles that arise in their activities while achieving their goals. It has been established that the problem of the formation of students' volitional qualities is one of the most urgent, since volitional qualities play an important role in the development of a personality, and physical culture lessons and its means are effective in solving this problem. The manifestation of volitional qualities largely depends on the confidence of students in their abilities, their motivation and the ability to make volitional efforts. Emphasis is made on the increase in the level of formation of volitional qualities (courage, self-affirmation, independence) is largely achieved due to the specifics of tennis. After all, in the process of playing tennis, students develop moral, volitional and physical qualities. In addition, a tennis player must master the ability to instantly switch and distribute attention, plan next steps and more. All this requires effort and constant overcoming of difficulties, as it is necessary to be able to quickly and accurately navigate and assess the game environment, make effective decisions independently and anticipate the results. In performing tactical actions by tennis players, their creative thinking, memory and imagination are realized, which contributes to development the boldness, self-affirmation and independent way of making decisions. It is also noted that one of the productive forms of development of boldness, affirmation and independence is also practicing games which include elements of tennis. This type of games is effective for upbringing students’ discipline, boldness, self-affirmation and independence.